Comparative evaluation of fracture resistance of various post systems using different luting agents under tangential loading - Rajnish Aggarwal; Swati Gupta; Amrit Tandan; Narendra Kumar Gupta; Ravi Dwivedi; Renu Aggarwal (Journal of Oral Biology and Craniofacial Research)
Objective: The purpose of this in vitro study was to evaluate the fracture resistance of various post system using different luting agents under tangential loading after wet thermocycling. Material & methods: Seventy freshly extracted maxillary central incisors were endodontically treated and post-spaces were prepared to receive different post system. They were assigned to 7 groups. Composite resin was used as core material in all the groups. Three type of post system: prefabricated post system (ParaPost® XP™), fibre post (ParaPost® fiber Lux™), cast nickel–chromium alloy post and two type of luting cements dual cure resin cement (ParaCem®, Whaledent) and glass ionomer cement (Fuji I, GC) were used. The specimens were thermocycled and subjected to tangential loading at a crosshead speed of 1.5 mm/min. The failure loads were recorded and data were statistically analyzed with one-way ANOVA (p < 0.05) and Student's t tests (p < 0.001). Results: Significant differences of fracture resistance were detected among groups (p < 0.001). The greatest number of repairable fracture mode was recorded in fibre posts and resin cement system. Conclusions: Within the limitations of this in vitro study, it can be stated that fibre posts can be recommended as a better alternative to the cast post and cores and prefabricated metallic posts in the anterior region and resin cement might give additional fracture resistance when used for post and crown cementation.